MicroRNA-7 upregulates death receptor 5 and primes resistant brain tumors to caspase-mediated apoptosis. Issue 2 (25th July 2017) - Bhere, Deepak; Tamura, Kaoru; Wakimoto, Hiroaki; Choi, Sung Hugh; Purow, Benjamin; Debatisse, Jeremy; Shah, Khalid
Abstract: Background: MicroRNAs (miRs) are known to play a pivotal role in tumorigenesis, controlling cell proliferation and apoptosis. In this study, we investigated the potential of miR-7 to prime resistant tumor cells to apoptosis in glioblastoma (GBM). Methods: We created constitutive and regulatable miR-7 expression vectors and utilized pharmacological inhibition of caspases and genetic loss of function to study the effect of forced expression of miR-7 on death receptor (DR) pathways in a cohort of GBM with established resistance to tumor necrosis factor apoptosis inducing ligand (TRAIL) and in patient-derived primary GBM stem cell (GSC) lines. We engineered adeno-associated virus (AAV)–miR-7 and stem cell (SC) releasing secretable (S)-TRAIL and utilized real time in vivo imaging and neuropathology to understand the effect of the combined treatment of AAV–miR-7 and SC–S-TRAIL in vitro and in mouse models of GBM from TRAIL-resistant GSC. Results: We show that expression of miR-7 in GBM cells results in downregulation of epidermal growth factor receptor and phosphorylated Akt and activation of nuclear factor-kappaB signaling. This leads to an upregulation of DR5, ultimately priming resistant GBM cells to DR-ligand, TRAIL-induced apoptotic cell death. In vivo, a single administration of AAV–miR-7 significantly decreases tumor volumes, upregulates DR5, and enables SC-delivered S-TRAIL to eradicate GBM xenografts generated from patient-derived TRAIL-resistant GSC, significantly improving survival of mice. Conclusions: This study identifies the unique role of miR-7 in linking cell proliferation to death pathways that can be targeted simultaneously to effectively eliminate GBM, thus presenting a promising strategy for treating GBM.